Small carnivore diversity in forest patches around oil palm plantation in West Sumatra, Indonesia - Inda Dwi Solina; Erizal Mukhtar; Wilson Novarino; Dahelmi Dahelmi (Society for Indonesian Biodiversity, 2023)
Abstract. Solina ID, Mukhtar E, Novarion W, Dahelmi. 2023. Small carnivore diversity in forest patches around oil palm plantation in West Sumatra, Indonesia. Biodiversitas 24: 1824-1832. The accelerating rates of forest conversion into agricultural land are the main driver for biodiversity loss. How biodiversity, particularly secondary consumers, can adapt to different agricultural schemes is critical to conservation planning. Currently, small forests within oil palm plantations should receive more attention, especially as they are habitats for small carnivores, and it is still unknown how they respond to habitat change. We analyzed camera trap data from 2015 to 2018 in key High Conservation Value (HCV) forests in South Solok, West Sumatra: Kencana Sawit Indonesia company (forest patch A) and Tidar Kerinci Agung company (forest patches B and C). LecoS is used to collect landscape metrics data then evaluated using the Generalized Linear Models (GLM) to assess the impact of fragmentation on the presence of small carnivores in forest patches. The model with the lowest Akaike Information Criterion (AIC) value was the one we regarded to be the most acceptable. We found 12 species of small carnivores belonging to 4 families; six species were identified in patch A, ten in patch B, and only three in patch C. We identified that land covers are the most important parameter on the presence of small carnivores in oil palm plantations in West Sumatra based on GLM results. Due to the importance of forested regions to small carnivore diversity, we recommend increasing forest connectivity into and across oil palm landscapes.